Morphological and molecular characterization of Crassicauda anthonyi in Cuvier’s beaked whales from the Canary Islands - Z. Suárez-González; A. Fernández; A. Colom-Rivero; N. García-Álvarez; J. F. González; E. Sierra (BMC Veterinary Research)
Abstract Cuvier's beaked whale (CBW) (Ziphius cavirostris) is a cosmopolitan species known for its remarkable diving capabilities and is widely distributed across most seas and oceans, including the waters surrounding the Canary Islands. This species frequently exhibits a high prevalence of parasitism by the nematode Crassicauda spp., which affects the kidney, urinary tract, and arterial walls via larval migration, and is considered one of the primary natural causes of mortality among CBWs in the Canary archipelago. Despite its significance, molecular identification of this parasite in the Canary Islands has not been systematically conducted until now. To address this gap, 51 CBW’s stranded in the Canary Islands between 1999 and 2023 were necropsied, and 11 adult nematodes were collected from the kidneys of 11 CBWs. Morphological identification and molecular analyses targeting the mitochondrial COX1 gene and the ITS-2 region were performed, with phylogenetic relationships within the genus Crassicauda assessed. Adult parasitism was observed in 86% of the examined animals. Morphological examination identified the species as Crassicauda cf. anthonyi, which was corroborated by molecular analyses as Crassicauda anthonyi. Renal nodular lesions associated with parasitism were characterized by granulomatous inflammation of varying severity, with intralesional nematodes, fibrosis, necrosis, and multifocal mineralization. Crassicauda anthonyi demonstrates a high prevalence and host specificity, contributing to significant renal pathology in stranded CBWs. This study provides parasite morphological data and molecular identification of C. anthonyi in the Canary Islands, enhances understanding of its prevalence, and expands both the taxonomy and genetic sequence database for the Crassicauda genus.